PSYCHOLOGICAL IMPACT ON PRIMARY HYPOTHYROIDISM: GENDER DIFFERENCES IN ANXIETY, DEPRESSION AND STRESS - VADAREVU SONY; BALASASIREKHA.R (The Journal of Research ANGRAU, 2025)
The study was conducted in the year 2024 to emphasis on prevalence of anxiety, depression and stress in hypothyroidism patients. Thestudy included a convenient sample of 100 hypothyroid patients aged between 20-60 years, encompassing both male and femaleparticipants. The results conferred that with respect to Body Mass Index (BMI), majority (46.87%) of the female respondents were fell under overweight category, whereas, 38.88 per cent of male respondents were found under pre-obese category. Whereas, in case of anxiety among hypothyroid subjects, both the gender reported similar feelings in-terms of numbness (62.00%) and heartbeat (46.00%). In case of depression, 71 per cent of females expressed that they had lost interest in everything, whereas 61 per cent of the male felt sad. With regard to stress, 75 per cent of females expressed that they couldnot tolerate the interruptions during working time. In case of males, majority of them (66.00%) expressed that stress full events cause problem in relationship with other people